Deutschland im Herbst (1978) & Die Patriotin - Kluge, Alexander; Schlöndorff, Volker; Fassbinder, Rainer Werner; Böll, Heinrich (München : Edition Filmmuseum, 2008)
Deutschland im Herbst (Germany in Autumn): A collective film chronicling seven weeks of political terrorism by the Red Army Faction and political repression in Germany during the fall of 1977. It begins with the kidnap and murder of industrialist Hans-Martin Schleyer and ends with the deaths of three imprisoned Baader-Meinhof terrorists. Includes the work of many of Germany’s top directors. ##Die Patriotin (The patriot): Various aspects of German history are explored from several angles in a series of odd sequences. Gabi Teichert (Hannelore Hoger) is both a history teacher and a patriot. One day she goes out into the winter landscape carrying a shovel (digging for the truth?) and comes across a dead soldier killed at the battle of Leningrad, whose symbolically disembodied knee speaks to her. Next, Gabi scans the landscape with a telescope, looking for evidence. Later, she is at a convention of the Social Democrat Party and tries to find information there. The scenes continue at different venues and with different people as this history teacher tries to piece together history. ##Deutschland im Herbst / Germany in Autumn (119 min.), 1978 -- Nachrichten von den Staufern (22 min.), 1977 -- Die Patriotin / The Patriot (118 min.), 1979 -- Die Menschen, die das Staufer-Jahr vorbereiten (39 min.), 1977.
Onderzoek KASK Professioneel (OFVP)
Duits gesproken, ondertitels in Engels, Frans, Russisch, Chinees en Spaans
film
Keywords: Kluge, Alexander